Condutas ambientais de uma família camponesa na Colônia Treze-Lagarto/SE - Souza, Alessandra Barbosa (2025)
The themes involving the socio-environmental issue have gained diverse spaces for discussion in the search for harmonious alternatives in the relationship between society and nature. In this context, reflecting on the peasant and their unique way of life requires a broader perspective, a historical review, and the understanding of certain concepts that support this broad theme, such as: the construction of the concept of the peasant as a multifaceted subject; their ethical conduct, which is essential in the consolidation of ecologically sustainable practices; social learning as a means of building and sharing knowledge, where peasants act as active and participatory subjects in society; and finally, ecological resilience, which enables them to overcome the adversities of rural life. Thus, the general objective was established as: to examine the environmental conduct of a peasant family living in Colônia Treze, Lagarto, Sergipe. To this end, we defend the thesis that the peasant, rooted in traditional knowledge, possesses a way of life that, through principles consolidated in daily practices, expresses a deep peasant ecology and guides sustainable environmental behavior. This form of existence establishes a relationship of belonging, care, and reverence toward nature, understanding the land not as a resource to be exploited, but as a living being with whom one lives in reciprocity and respect. The research was based on a phenomenological approach, focusing on the lived experience of a peasant family and their interaction with the environment, the presence and influence of ethics in their way of life, considering the dynamics of social learning and ecological resilience, as well as the elements that contribute to the adoption of sustainable environmental practices.This study was carried out in stages: immersion in the research locus with participant observation, aligned with a bibliographic review; then the empirical research, including field visits, informal conversations, and photographic and audio recordings, was guided by social phenomenology and the oral history method; and finally, the critical and interpretative analysis of the narratives included throughout the text, presenting a lived peasant experience that highlights a particular way of life in harmony with nature, especially in times when capitalism acts in a devastating manner.We conclude that the interaction between ethical conduct, social learning, and ecological resilience constitutes a fundamental tripod for the adoption of sustainable environmental practices in the peasant daily life. These three elements do not operate in isolation but complement one another, creating a model of coexistence with the land that combines tradition and innovation among these peasant guardians of life.